Efficacy and safety of Saccharomyces boulardii CNCM I-745 for the treatment of pediatric acute diarrhea in China: a systematic review and meta-analysis - McFarland, Lynne V.; Li, Tong (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPediatric acute gastroenteritis (PAGE) is a common cause of morbidity and mortality, especially in children under five years old. Therapeutic strategies including probiotics have been investigated, but trials from non-English speaking countries may not be easily accessible.AimTo determine the efficacy of Saccharomyces boulardii compared to controls for treating PAGE in children receiving standard rehydration therapy in trials conducted in China.MethodsSystematic review and meta-analysis using literature search with Google Scholar, PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure and China Biology Medicine disc (from inception to June 30, 2024) of randomized, controlled trials comparing S. boulardii CNCM I-745 to controls for the treatment of PAGE in children conducted in China. Independent data extraction by two reviewers. Standard meta-analysis methods were applied and random-effect or fixed-effects models were used depending upon the degree of heterogeneity using standardized mean differences for continuous data and relative risk estimates for dichotomous outcomes. The risk of bias for each study was determined and heterogeneity was measured by I2.ResultsOf 851 articles screened, 10 RCTs (1125 participants) met the inclusion criteria, and none were found in non-Chinese databases. S. boulardii CNCM I-745 was found to significantly reduce the duration of PAGE (SMD=-1.63 days, 95% CI -2.08, -1.18), improve the total effectiveness rating (RR=1.22, 95% CI 1.16, 1.28) and significantly more participants were cured (RR=1.47, 95% CI 1.30, 1.67). The finding that S. boulardii significantly reduced the levels of two pro-inflammatory cytokines (TNF-α and IL8) has not been reported in previous meta-analyses of PAGE.ConclusionS. boulardii CNCM I-745 is an effective treatment for PAGE and was well tolerated in trials done in China.Systematic review registrationwww.crd.york.ac.uk/PRSPERO, identifier CRD 42024567537.